2020
DOI: 10.1101/2020.08.10.20171629
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk of fomite-mediated transmission of SARS-CoV-2 in child daycares, schools, and offices: a modeling study

Abstract: SARS-CoV-2 can persist on surfaces, suggesting that surface-based transmission might be important for this pathogen. We find that fomites may be a substantial source of risk, particularly in schools and child daycares. Combining surface cleaning and decontamination with strategies to reduce pathogen shedding on surfaces can help mitigate this risk.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…Fomite transmission was amplified by subsequent cohabitation of rats. Conflicting data exist regarding the risk of fomite transmission in SARS-CoV-2 [27,46]. Our data indicate that while comparatively low, this route represents a clear source of transmission risk in that can be amplified by close contact such as dense co-housing conditions.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Fomite transmission was amplified by subsequent cohabitation of rats. Conflicting data exist regarding the risk of fomite transmission in SARS-CoV-2 [27,46]. Our data indicate that while comparatively low, this route represents a clear source of transmission risk in that can be amplified by close contact such as dense co-housing conditions.…”
Section: Discussionmentioning
confidence: 68%
“…SDAV infects salivary glands [21], a capacity recently demonstrated for SARS-CoV-2 [42]. Both SARS-CoV-2 and SDAV can persist on hard surfaces for up to 28 days [27,43] and 2 days [44] respectively. Like SARS CoV-2 [24][25][26][27][28], SDAV infection can be transmitted by asymptomatically infected individuals [29] via airborne, direct contact or fomite routes [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xiao et al went on to analytically investigate how fomite transmission of SARS infections were found to play a non-negligible role in pathogen transmission throughout a simulated hospital setting. The study by Xiao et al is only one of a number of similar works attesting to the fact that preventative measures need to be taken to minimize the risk of infection associated with touching an infected surface when SARS-based coronavirus outbreaks occur [2][3][4][5] . Otter et al found that SARS-CoV, MERS-CoV, and the influenza virus was shed from an infected community member within a hospital-like setting at concentrations that are much greater than the dose required for infection 6 .…”
Section: Fomite Transmission Of Viral Pathogens and Sars-cov-2mentioning
confidence: 99%
“…With particular attention being given to SARS-CoV-2 and similar viruses, Castaño et al focused on disinfection approaches to inhibit surface-contact mediated fomite transmission in 7 . Additional works of scholarship worth consideration include 4,[8][9][10][11][12][13][14] . Ciacotich et al published an analysis of the antibacterial efficacy of an alloyed copper coating with silver as the alloying element in 18 .…”
Section: Fomite Transmission Of Viral Pathogens and Sars-cov-2mentioning
confidence: 99%